Implications for the dynamics of slopes from the evolution of the vineyards terraces of Douro Wine Region (Portugal) - Rodrigues, Silvio Carlos; Pedrosa, António de Souza (Sociedade & Natureza, 2016)
he evolution of land use activities to wine from the Douro River (PT) is closely tied to its geomorpho-logical structure because on the one hand depends on the configuration of the slopes and on the other, the conditions of weathering of rocks and formation of surface mantles. Human action over time, created 5 different types of terraces, adapted to technological conditions of appropriation of land: Pré-filox-éricos, Pós-filoxéricos (traditional), Patamares, Curvas de Nível e Vinha ao Alto. These modalities of implementation of the vineyards eventually change the conditions of stability of slopes by modifying the hydrodynamic conditions and allowing increased of high intensity of erosion. As a result, it was ob-served that the ancient implementations, not cause so many situations of no equilibrium of the slopes, a phenomenon that has its culmination in the patamares type, because they present a greater alteration of the natural conditions of the slopes related to the large soil movement and the construction of embank-ments on high ground because they are often allocated on slopes with very steep slopes.